On one algorithm for solving the problem of source function reconstruction - Maksimov, Vyacheslav I. (Zielona Góra: Uniwersytet Zielonogórski)
In the paper, the problem of source function reconstruction in a differential equation of the parabolic type is investigated.Using the semigroup representation of trajectories of dynamical systems, we build a finite-step iterative procedure forsolving this problem. The algorithm originates from the theory of closed-loop control (the method of extremal shift). Atevery step of the algorithm, the sum of a quality criterion and a linear penalty term is minimized. This procedure is robustto perturbations in problems data.
Keywords: reconstruction; source function; feedback control